Autoimmunity in narcolepsy. Issue 6 (November 2017) - Bonvalet, Melodie; Ollila, Hanna M.; Ambati, Aditya; Mignot, Emmanuel
Abstract : Purpose of review: Summarize the recent findings in narcolepsy focusing on the environmental and genetic risk factors in disease development. Recent findings: Both genetic and epidemiological evidence point towards an autoimmune mechanism in the destruction of orexin/hypocretin neurons. Recent studies suggest both humoral and cellular immune responses in the disease development. Summary: Narcolepsy is a severe sleep disorder, in which neurons producing orexin/hypocretin in the hypothalamus are destroyed. The core symptoms of narcolepsy are debilitating, extreme sleepiness, cataplexy, and abnormalities in the structure of sleep. Both genetic and epidemiological evidence point towards an autoimmune mechanism in the destruction of orexin/hypocretin neurons. Importantly, the highest environmental risk is seen with influenza-A infection and immunization. However, how the cells are destroyed is currently unknown. In this review we summarize the disease symptoms, and focus on the immunological findings in narcolepsy. We also discuss the environmental and genetic risk factors as well as propose a model for disease development.